COVID-19 first anniversary review of cases, hospitalization, and mortality in the UK. (3rd August 2021) - Merchant, Hamid A.; Kow, Chia Siang; Hasan, Syed Shahzad
ABSTRACT: Introduction : The first confirmed COVID-19 case in UK dates to 11 January 2020, exhibiting its first peak during April 2020. The country has since been hit by another wave in the winter 2020, almost at the first anniversary of the pandemic. Areas covered: An in-depth analysis of the COVID-19 positive cases in the UK throughout the year, hospitalizations, patients in critical care, and COVID-19 associated deaths. Expert opinion : The COVID-19 associated hospital admission accounts to 15% of total COVID-19 positive cases in November 2020. The percentage of total COVID-19 positive patients in the country died from the disease was under 4% in November 2020. Total deaths in England (all-cause) from June to October 2020 were similar to the historic averages. Age was the single most determinator of COVID-19 associated mortality, 50 years or older accounted for 98% of total COVID deaths. Age distribution of COVID-19 associated deaths in 2020 was similar to all-cause mortality age distribution in 2019. There was no significant improvement in the survival rate of COVID-19 patients receiving critical care. This prompts an urgent need to invest in novel antiviral therapeutics to save the most vulnerable in the society.